2018
DOI: 10.1021/acssuschemeng.7b03617
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Rheological, Thermal, and Solid-State Properties of Branched PLA by Free-Radical-Mediated Reactive Extrusion

Abstract: The purpose of this work is to establish structure–property relations of poly­(lactide) (PLA) formulations that were branched by peroxide-mediated reactive extrusion, in the presence of triallyl trimesate (TAM) coagent. Based on detailed evaluations of the molar mass distributions and rheological properties we deduce that modified PLA consists of a population of linear, and long chain branched (LCB) PLA chains, depending upon the amount of the peroxide and coagent. Even though peroxide alone does not induce si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…It has been documented that radical‐mediated coagent modifications in polyolefin systems yield bimodal molecular weight and branching distributions. [ 37,61–63 ] Similarly, it has been suggested that two types of chain populations are present in coagent‐modified PLA [ 42,46,64,65 ] : linear chains, which remain unreacted, and LCB structures that are generated through combination of the tri‐functional coagent with the PLA macroradicals (Scheme 2). The latter typically appear in the form of bimodal molar mass distributions, resulting in deviations from the M‐H relationship (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been documented that radical‐mediated coagent modifications in polyolefin systems yield bimodal molecular weight and branching distributions. [ 37,61–63 ] Similarly, it has been suggested that two types of chain populations are present in coagent‐modified PLA [ 42,46,64,65 ] : linear chains, which remain unreacted, and LCB structures that are generated through combination of the tri‐functional coagent with the PLA macroradicals (Scheme 2). The latter typically appear in the form of bimodal molar mass distributions, resulting in deviations from the M‐H relationship (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Estimation of the branching content by using the Zimm‐Stockmayer equation, revealed that branching resides in the high molecular weight fractions. [ 64,66 ] Detailed characterization showed that the efficacy of the coagents was in the order TAM~TAC>TMPTA>PETA>TMPTMA. [ 57,66 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the preparation of PLA blends or PLA composites, free‐radical reactions initiated by various initiators are often employed to enhance the interfaces between immiscible polymers or between polymer matrix and fillers. Considering the high activities of the initiators, they are always applied in reactive extrusion or preparation of PLA blends [23,24]. Through the reactions, PLA is directly bonded with other immiscible polymers [24] or modified with small molecules, which work as a compatibilizer, such as maleic anhydride (MA) [25].…”
Section: Introductionmentioning
confidence: 99%